WEAVING A FRAGILE SAFETY NET: THE TRIANGULAR APPROACH FOR STRENGTHENED HEALTH AND SAFETY PROTECTION FOR PLATFORM WORKER - Zahra, Annisa Fathima; Grasiaswaty, Novika (Faculty of Law Atma Jaya Yogyakarta University, 2025)
Platform workers in Indonesia face a significant dilemma, particularly regarding employment security. Being classified as independent workers means they do not receive the same protections and benefits as regular employees in Indonesia. If employment security and benefits are seen as a safety net for employees in difficult situations, for platform workers in Indonesia, that net is fragile—prone to breaking at any moment. To address this dilemma, this study employs a juridical-normative and conceptual research approach to explore alternatives to legal enforcement. The findings suggest that if sanctions on platform companies and workers prove ineffective, reward mechanisms—such as a “Zero Accident Award”—could motivate platform companies to encourage worker participation in BPJS Ketenagakerjaan (social security). By offering recognition and public rewards, this soft law approach can increase compliance and improve worker protection without changing the legal status of platform workers. Additionally, the community award for platform workers to increase awareness of individual registration is also encourages. In a rapidly evolving digital economy, such strategies could help address gaps where traditional legal frameworks are inadequate.